Estimating the impact of immigration on wages in Ireland - Barrett, Alan; Bergin, Adele; Kelly, Elish (Economic & Social Studies, 2011)
We estimate the impact of immigration on the wages of natives in Ireland applying the technique proposed by Borjas (2003). Under this method, the labour market is divided into a number of skill cells, where the cells are defined by groups with similar ages and levels of education (or age and occupation). Regression analysis is then employed to assess whether the average wages of natives across skill cells is affected by the share of immigrants across cells. When the cells are based on education/age, our results suggest a negative relationship between native wages and immigrant shares. However, the opposite appears to hold when the cells are based on occupation/age. These contradictory findings suggest that care should be exercised when applying this method as inaccurate impressions of the impact of immigration on wages may arise.
Keywords: Immigration; Wages; Ireland